Inflammation and cardiovascular status impact midazolam pharmacokinetics in critically ill children: An observational, prospective, controlled study - Bikalpa Neupane; Hitesh Pandya; Tej Pandya; Rupert Austin; Neil Spooner; James Rudge; Hussain Mulla (Wiley, 2022)
Abstract Altered physiology caused by critical illness may change midazolam pharmacokinetics and thereby result in adverse reactions and outcomes in this vulnerable patient population. This study set out to determine which critical illness‐related factors impact midazolam pharmacokinetics in children using population modeling. This was an observational, prospective, controlled study of children receiving IV midazolam as part of routine care. Children recruited into the study were either critically‐ill receiving continuous infusions of midazolam or otherwise well, admitted for elective day‐case surgery (control) who received a single IV bolus dose of midazolam. The primary outcome was to determine the population pharmacokinetics and identify covariates that influence midazolam disposition during critical illness. Thirty‐five patients were recruited into the critically ill arm of the study, and 54 children into the control arm. Blood samples for assessing midazolam and 1‐OH‐midazolam concentrations were collected opportunistically (critically ill arm) and in pre‐set time windows (control arm). Pharmacokinetic modeling demonstrated a significant change in midazolam clearance with acute inflammation (measured using C‐Reactive Protein), cardio‐vascular status, and weight. Simulations predict that elevated C‐Reactive Protein and compromised cardiovascular function in critically ill children result in midazolam concentrations up to 10‐fold higher than in healthy children. The extremely high concentrations of midazolam observed in some critically‐ill children indicate that the current therapeutic dosing regimen for midazolam can lead to over‐dosing. Clinicians should be aware of this risk and intensify monitoring for oversedation in such patients.